FACTORS RELATING TO DEPRESSION AMONG OLDER PEOPLE LIVING IN CIMAHI, WEST JAVA PROVINCE, INDONESIA - Kiki Gustryanti; Sunanta Thongpat; Sonthaya Maneerat (Belitung Raya Foundation, 2017)
Background: Depression is commonly found in older people. The prevalence of depression among older people, particularly in Indonesia is increasing worldwide. Objective: This study was aimed to identify the factors relating to depression among older people living in Cimahi, West Java Province, Indonesia. Method: A cross sectional design was used with a total of 267 older people aged from 60 to 79 years old. A multi-stage random sampling has been used in five Public Health Centers in Cimahi. The instruments comprised socio-demographic questionnaires, General Health Perceptions questionnaire, Chula Activities of Daily Living Index (CADLI), and Geriatric Depression Scale-15 (GDS-15). Data analysis was conducted using descriptive statistic, chi-square, and point-biserial. Results: The result revealed that 56.2% respondents was no depression and 43.8% respondents was depression. The results also showed that age, marital status, family history of depression, perceived health status, and activities of daily living was significant relationship with depression a mong older people (p<.01; p<.05). Conclusion: This finding can be used as a reference to implement new strategies to decrease depression among older people.